Symbiotic Interactions in the Multi-ethnic Settlements in Semarang, Indonesia - Susanti, Anityas Dian; Setiawan, Bakti; Widyastuti, Dyah Titisari (Center for Cities, University of Moratuwa, 2023)
Symbiotic interactions in multi-ethnic settlements are the dominant aspect of the settlements in the city of Semarang, where there are interactions among the three ethnic communities: the Koja, the Javanese, and the Chinese. The issue in multi-ethnic settlements is to ensure the formation of a mutually-beneficial, good symbiosis of inter-ethnic interactions. This paper examines the nature of the symbiosis of the interactions among the multi ethnic communities in Semarang. It raises the question as to what activities are included in the symbiotic interactions and what are their current conditions? The research uses phenomenology, and looks closely at the phenomenon of symbiotic interactions in the city of Semarang. Data collection involved observations of the research object and in-depth interviews with the communities. The findings of the research show that the dominant symbiotic interactions are cultural, economic, and religious. The paper argues that it is the characteristic or uniqueness in multi-ethnic settlements, as divulged in the city of Semarang